PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR MATA PELAJARAN PEKERJAAN DASAR OTOMOTIF MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD - Maduma Acarige Dihren Awdiassoleh; Slamet Priyanto (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2020)
The study aims to determine: (1) the application of STAD cooperative learning model; (2) the improvement of learning activeness; and (3) the improvement of learning basic automotive work achievement.This research was a classroom action research. The technique of collecting data used observation, tests anddocumentation. The data analysis technique uses quantitative analysis. The results showed that: (1) theapplication of the STAD model in learning basic automotive jobs in the first cycle was classified as sufficient %,increasing in the second cycle in good criteria, and increasing in the third cycle in the criteria very good; (2)Implementation of STAD model can increase learning activeness. The average percentage of learning activenessin the first cycle was in active enough, increasing in the second cycle with the active category, and increasingagain in the third cycle with very active criteria; (3) The application of STAD model increases the learningachievement of basic automotive work. The average value of learning achievement was incerased in pre-action,cycle I, cyle II, and cycle III.Keywords: STAD, Activity, Learning Achievement